Co-combustion of coal and biomass in a fluidised bed reactor - García Fernández, Luis Eduardo (2019)
For decades coal has been the main energy source for electricity generation in many parts of the world. Coal combustion is the most intensive producer of CO2, the main greenhouse gas (GHG) in the atmosphere. The continued dominance of fossil fuels, particularly coal, in the energy mix has been going on for decades due to the slow uptake of low-carbon technologies. Among others, co-combustion of coal and biomass is quite a promising alternative in the short-term to achieve major cuts in GHG and pollutant emissions. Nevertheless, the current inability to address technical factors linked to the characteristics of biomass in terms of ash issues during combustion or modification of ash quality limits the increase of biomass ratio in co-combustion. The pursuit of new resources to substitute coal has prompted consideration of the use of woody materials, herbaceous biomass or waste from the agroindustrial sector.